The Changing Pattern of Pediatric Both-Bone Forearm Shaft Fractures among 86,000 Children from 1997 to 2009 - Sinikumpu, Juha-Jaakko; Pokka, Tytti; Serlo, Willy (European Journal of Pediatric Surgery, 2013)
Introduction Forearm fractures are common among children. Unlike most pediatric fractures, there is a risk of unsatisfactory results in forearm shaft fractures. The healing of a tubular bone is most unlikely in the diaphysis far away from the metaphyseal zones. The treatment of forearm shaft fractures is evolving. The purpose of the study was to analyze the pattern of forearm shaft fractures and their treatment in a population of children in recent years.Materials and Methods All the children (from 0 to 16 years) with a both-bone forearm shaft fracture (AO-segment 22-D) during the years 1997 to 2009 in a catchment area of about 86,000 children were included in this population-based study. There were 291 fractures in all. The age-related annual incidences, background factors, seasonal variation, injury types, treatment, reoperations, and short-term outcome were determined.Results The incidence of all forearm shaft fractures increased threefold in 1997 to 2009 (p < 0.001). Boys predominated (70%) over the girls (p < 0.001). The mean age of the patients was 8.7 years (SD, +/− 3.8) among both genders. The fractures were most common in August and most uncommon in December (p < 0.001). A fall in the playground was the most common type of injury (34%). Ninety-two percent of all patients (N = 269) were treated in the operating room and 44% (N = 119) were invasively stabilized. The incidence of invasive surgery held stable. However, elastic stable intramedullary nailing (ESIN) increased from 10% in 1998–2000 to 30% in 2007–2009 (p = 0.043). There were 77 reoperations (26%); reoperation rate was 5% (6/119) and 41% (N = 71/172) in the invasive and non-invasive treatment groups, respectively. Twenty-three percent of the patients referred did not have better than “good” short-term results. The “excellent” short-term outcome was increasing (p = 0.031).Conclusions We found two mega-trends in pediatric forearm shaft fractures in the period from 1997 to 2009: First, the number of fractures was increasing significantly. Second, the forearm shaft fractures were increasingly treated by an invasive intramedullary method. We also found a significant seasonal variation, but the reason for it is not clear. The findings are based on valuable population-based data and the results are certain. Pediatric trauma centres should prepare themselves for on-going changes in forearm shaft fractures.
Keywords: forearm fracture; epidemiology; children; surgical treatment; both-bone